Lithium borohydride-lithium iodide composite solid electrolyte material as well as preparation method and application thereof

The preparation of lithium borohydride-lithium iodide composite solid electrolyte material in anhydrous tetrahydrofuran by liquid phase method has solved the problems of high energy consumption and low yield in the prior art, achieved efficient and large-scale production, and improved the ionic conductivity and purity of the material.

CN119674203APending Publication Date: 2025-03-21ZHEJIANG BAIMA LAKE LABORATORY CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411900904.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-11-19
Filing Date
2024-12-23
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The existing preparation methods of lithium borohydride-lithium iodide solid electrolyte materials rely on high-energy ball milling and subsequent heat treatment, resulting in high energy consumption, low output and inability to produce on a large scale, which seriously restricts its application potential.

Method used

Lithium borohydride is added to the anhydrous tetrahydrofuran solvent by liquid phase method first and then anhydrous lithium iodide. The trace amount of water in tetrahydrofuran is removed by lithium borohydride to ensure the purity of the sample, and the composite solid electrolyte material is obtained by vacuum solvent removal and heat treatment.

Benefits of technology

It improves doping efficiency, improves ionic conductivity, realizes large-scale production, and ensures high purity and excellent performance of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119674203A_ABST
    Figure CN119674203A_ABST
Patent Text Reader

Abstract

The invention relates to the field of electrolyte, and provides a lithium borohydride-lithium iodide composite solid electrolyte material as well as a preparation method and application thereof. The preparation method comprises the following steps: A, adding lithium borohydride into a solvent anhydrous tetrahydrofuran for dissolving, and then adding lithium iodide to form a uniform solution; b, transferring the solution into a closed container, and removing the solvent in vacuum until the solution is converted into a solid; and carrying out heating heat treatment to obtain the composite solid electrolyte material. According to the method, a liquid phase method is adopted, lithium borohydride is firstly added into an anhydrous tetrahydrofuran solvent, then anhydrous lithium iodide is added into the anhydrous tetrahydrofuran solvent, and trace water in tetrahydrofuran is removed by using lithium borohydride, so that the sample purity is ensured, and the ionic conductivity of the material is improved. The invention also provides an application of the lithium borohydride-lithium iodide composite solid electrolyte material in an all-solid-state battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of electrolytes, and in particular to a lithium borohydride-lithium iodide composite solid electrolyte material and a preparation method and application thereof. Background Art

[0002] Lithium-ion batteries frequently have safety accidents, which are mainly caused by high-temperature flammable organic electrolytes. The development of all-solid-state lithium-ion batteries can fundamentally solve this safety hazard. Therefore, the development of non-flammable all-solid-state lithium-ion batteries is the inevitable direction for achieving the next generation of batteries with high safety, high energy density, high power density and long cycle life. The development and application of solid-state electrolytes are the key to all-solid-state batteries. Lithium borohydride-lithium iodide solid electrolytes have attracted much attention due to their excellent stability, high ionic conductivity, wide potential window and excellent mechanical properties.

[0003] However, the main preparation method of lithium borohydride-lithium iodide solid electrolyte relies on high-energy ball milling and subsequent heat treatment. For example, patent CN111180789A discloses a composite solid electrolyte material and its preparation method and application, in which the prepared lithium borohydride, lithium iodide and manganese sulfide are mixed and ground in an atmosphere where the oxygen content and water content meet the preset conditions. This method has high energy consumption and is also limited by the capacity of the ball milling equipment. The output is usually at the milligram level, and the whole process needs to be carried out in an inert gas atmosphere, which cannot be mass-produced, seriously restricting its application potential. Therefore, an ideal solution is needed. Summary of the invention

[0004] The invention provides a lithium borohydride-lithium iodide composite solid electrolyte material and a preparation method and application thereof. A liquid phase method is adopted to first add lithium borohydride and then add anhydrous lithium iodide into an anhydrous tetrahydrofuran solvent, and the lithium borohydride is used to remove trace water in the tetrahydrofuran, thereby ensuring the purity of the sample and improving the ion conductivity of the material.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions: The method for preparing lithium borohydride-lithium iodide composite solid electrolyte material comprises the following steps: A. Add lithium borohydride into anhydrous tetrahydrofuran solvent to dissolve it, and then add lithium iodide to form a uniform solution; B. Transfer the solution to a sealed container, remove the solvent in vacuum until the solution is converted into a solid; heat treatment is performed at a high temperature to obtain a composite solid electrolyte material.

[0006] Preferably, the molar ratio of lithium borohydride to lithium iodide is 2-4:1, more preferably 3:1.

[0007] Preferably, the ratio of the volume of anhydrous tetrahydrofuran to the mass of lithium borohydride and lithium iodide is 2-8 mL:1 g, and the water content of anhydrous tetrahydrofuran is less than 50 ppm.

[0008] Preferably, the dissolution temperature is 10-60°C, and a uniform solution is formed by stirring for 3-48 hours.

[0009] Preferably, the sealed container is a glass reaction tube with a valve.

[0010] Preferably, the temperature at which the solution is converted into the solid stage is 10-60°C.

[0011] Preferably, the heat treatment temperature is 80-150°C and the time is 6-48h.

[0012] Preferably, the heating rate is 2-4°C / min.

[0013] The present invention also provides a lithium borohydride-lithium iodide composite solid electrolyte material, which is prepared by the above preparation method.

[0014] The invention also provides application of lithium borohydride-lithium iodide composite solid electrolyte material in composite solid electrolyte.

[0015] The present invention also provides application of lithium borohydride-lithium iodide composite solid electrolyte material in all-solid-state batteries.

[0016] Therefore, the beneficial effects of the present invention are: (1) The liquid phase method is used to prepare lithium borohydride-lithium iodide composite solid electrolyte materials, which helps to improve doping efficiency and ionic conductivity; and can also achieve large-scale production.

[0017] (2) First add lithium borohydride and then add anhydrous lithium iodide to tetrahydrofuran. Lithium borohydride can be used to remove trace water in tetrahydrofuran to ensure the purity of the sample. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 This is the XRD diagram of the lithium borohydride-lithium iodide composite electrolyte material obtained in Example 1.

[0019] Figure 2 This is a SEM image of the lithium borohydride-lithium iodide composite electrolyte material obtained in Example 1.

[0020] Figure 3 This is the electrochemical impedance diagram of the lithium borohydride-lithium iodide composite electrolyte material obtained in Example 1 at 40°C.

[0021] Figure 4 This is the electrochemical impedance diagram of the lithium borohydride-lithium iodide composite electrolyte material obtained in Example 1 at 120°C.

[0022] Figure 5 This is the XRD diagram of the lithium borohydride-lithium iodide composite electrolyte material obtained in Comparative Example 1.

[0023] Figure 6 This is the XRD diagram of the lithium borohydride-lithium iodide composite electrolyte material obtained in Comparative Example 2.

[0024] Figure 7 This is the electrochemical impedance diagram of the lithium borohydride-lithium iodide composite electrolyte material obtained in Example 2 at 40°C.

[0025] Figure 8 This is the electrochemical impedance diagram of the lithium borohydride-lithium iodide composite electrolyte material obtained in Example 2 at 120°C.

[0026] Fig. 9 This is the electrochemical impedance diagram of the lithium borohydride-lithium iodide composite electrolyte material obtained in Example 3 at 40°C.

[0027] Fig.10 This is the electrochemical impedance diagram of the lithium borohydride-lithium iodide composite electrolyte material obtained in Example 3 at 120°C. DETAILED DESCRIPTION

[0028] The technical solution of the present invention is further described below through specific embodiments.

[0029] In the present invention, unless otherwise specified, the raw materials and equipment used can be purchased from the market or are commonly used in the art. The methods in the embodiments, unless otherwise specified, are all conventional methods in the art. Unless otherwise specified, parts are all weight parts, temperatures are expressed in ° C or at ambient temperature, and pressures are atmospheric pressure or near atmospheric pressure. There are many variations and combinations of reaction conditions (such as component concentrations, desired solvents, solvent mixtures, temperatures, pressures, and other reaction ranges) and conditions that can be used to optimize the purity and yield of the product obtained by the method, and only reasonable routine experiments will be required to optimize such method conditions.

[0030] Example With the current urgent need for clean energy and sustainable development, the widespread use of liquid lithium-ion batteries has become an important driving force for electric vehicles, portable devices and renewable energy storage. However, the frequent safety accidents of lithium-ion batteries in recent years remain a major concern for the industry. These accidents are mainly caused by high-temperature flammable organic electrolytes, which make the battery prone to fire or explosion when the temperature reaches the ignition point of the organic solvent. This safety issue has always existed since the advent of lithium-ion batteries.

[0031] Recent studies have shown that the development of all-solid-state lithium-ion batteries can fundamentally solve this safety hazard, so researchers are paying more and more attention to the development of solid-state batteries. The advantage of all-solid-state batteries is that they do not contain flammable organic solvents, which significantly improves safety and avoids problems such as leakage, electrolyte drying and bloating. In addition, all-solid-state batteries are lighter, have higher energy density, and are more flexible in design and assembly. Therefore, the development of non-flammable all-solid-state lithium-ion batteries is the inevitable direction for achieving next-generation batteries with high safety, high energy density, high power density and long cycle life.

[0032] The development and application of solid electrolytes are the key to all-solid-state batteries. At present, solid electrolytes are mainly divided into two categories: organic and inorganic. Organic solid electrolytes have good flexibility and film-forming properties and are light in weight, but they perform poorly in mechanical properties and room temperature ionic conductivity. Relatively speaking, inorganic solid electrolytes have higher conductivity and a wider electrochemical window at room temperature, but their film-forming properties are insufficient. Among the many five-level solid electrolyte options, lithium borohydride-lithium iodide solid electrolytes have attracted much attention due to their excellent stability, high ionic conductivity, wide potential window and excellent mechanical properties. This is mainly due to the doping of lithium iodide, which allows lithium borohydride to maintain a high ionic conductivity at low temperatures, which is different from pure lithium borohydride, which can only exhibit high ionic conductivity in the high temperature phase.

[0033] However, the main preparation method of lithium borohydride-lithium iodide solid electrolyte relies on high-energy ball milling and subsequent heat treatment. This method has high energy consumption and is also limited by the capacity of the ball milling equipment. The output is usually at the milligram level, and the entire process needs to be carried out in an inert gas atmosphere, which cannot be mass-produced, seriously restricting its application potential. Based on this, the present invention proposes a preparation method and application of a lithium borohydride-lithium iodide composite solid electrolyte material.

[0034] 1. A method for preparing a lithium borohydride-lithium iodide composite solid electrolyte material The following steps are involved: Step 1: dissolve lithium borohydride in anhydrous tetrahydrofuran at 10-60°C, then add lithium iodide and stir for 3-48 hours to form a uniform solution.

[0035] Preferably, the water content of anhydrous tetrahydrofuran is less than 50 ppm. The volume of anhydrous tetrahydrofuran, the mass of lithium borohydride and lithium iodide and the ratio are 2-8 mL: 1 g.

[0036] The molar ratio of lithium borohydride to lithium iodide is 2-4:1. The composite solid electrolyte material of the present invention uses lithium borohydride as the main raw material. Lithium borohydride has the advantages of light weight, high temperature resistance, and low grain boundary resistance, but poor ion conductivity at room temperature. When lithium iodide is added, iodide ions replace part of the borohydride ions (BH4 -), so that lithium borohydride can maintain a hexagonal phase structure at room temperature. Therefore, the ratio of lithium borohydride and lithium iodide needs to be controlled within a reasonable range. When the molar ratio of lithium borohydride to lithium iodide is too small, the amount of lithium borohydride added as the main material is too small; when the molar ratio of lithium borohydride to lithium iodide is too large, less lithium iodide is introduced, so that part of BH4 is replaced by the addition of halogen ions. - The effect of reducing the phase structure transition temperature is not obvious. The present invention controls the molar ratio of lithium borohydride to lithium iodide to be in the range of 2-4:1, ensuring that the ion conductivity of the composite solid electrolyte material finally obtained at room temperature is high.

[0037] Step 2: Transfer the solution to a sealed container, remove the solvent in a vacuum at 10-60°C until the solution is converted into a solid; heat the temperature to 80-150°C at a heating rate of 2-4°C / min and heat treat for 6-48h to obtain a lithium borohydride-lithium iodide composite solid electrolyte material.

[0038] Preferably, the sealed container is a glass reaction tube with a valve.

[0039] The beneficial effects brought by the above preparation method include: 1) the liquid phase method is adopted, which is simple to operate, has low requirements on equipment, and can effectively break through the capacity limitation of high-energy ball milling equipment, thereby realizing large-scale production.

[0040] 2) By using a liquid phase mixing method, lithium borohydride and lithium iodide are evenly mixed at the molecular level, which helps to increase doping efficiency and improve ionic conductivity.

[0041] 3) Lithium borohydride is sensitive to water, so the whole process requires anhydrous and oxygen-free. However, the solvent anhydrous tetrahydrofuran will inevitably contain trace amounts of water (water content is less than 50 ppm), and even trace amounts of water will still affect the performance of the final product, lithium borohydride-lithium iodide composite solid electrolyte material.

[0042] Compared with lithium borohydride, lithium iodide has a stronger ability to bind water. Therefore, lithium iodide is added first or lithium borohydride and lithium iodide are added simultaneously. Lithium iodide will preferentially complex with trace water, resulting in the inability to remove these waters. The waters are present in the product lithium borohydride-lithium iodide composite solid electrolyte material, which reduces the purity of the product. The present invention first adds lithium borohydride and then lithium iodide to tetrahydrofuran, and lithium borohydride can be used to remove trace water in tetrahydrofuran to ensure sample purity. Specifically, lithium borohydride and water react to generate lithium hydroxide, boric acid and hydrogen, and hydrogen is released. The residual lithium hydroxide and boric acid have very little content on the one hand, and on the other hand, they can be used as electrolyte materials themselves, which have a promoting effect on the performance of solid electrolytes.

[0043] 4) In the solvent removal stage, first removing the solvent at low temperature can effectively prevent the occurrence of boiling, and then removing the solvent at high temperature can not only remove the residual solvent, but also promote the doping reaction.

[0044] 5) This method has the characteristics of low cost, low energy consumption, and environmental friendliness. It is very suitable for solid-state lithium-ion battery applications and has the feasibility of large-scale production.

[0045] 2. The lithium borohydride-lithium iodide composite solid electrolyte material is prepared by the above preparation method. At 40°C, the ion conductivity is 4.12×10 -5 S / cm.

[0046] 3. Application of lithium borohydride-lithium iodide composite solid electrolyte materials The lithium borohydride-lithium iodide composite solid electrolyte material prepared by the above preparation method is used for lithium borohydride-lithium iodide solid electrolyte.

[0047] The above-mentioned lithium borohydride-lithium iodide solid electrolyte is used in all-solid-state batteries.

[0048] Example 1 A method for preparing a lithium borohydride-lithium iodide composite solid electrolyte material, comprising the following steps: (1) Preparation of lithium borohydride / lithium iodide solution Anhydrous tetrahydrofuran with a water content of 50 ppm was used as solvent, lithium borohydride and lithium iodide were used as raw materials, and lithium borohydride (3.08 g) and lithium iodide (6.3 g) were weighed at a molar ratio of 3:1. Lithium borohydride was first dissolved in 50 mL of tetrahydrofuran solution, and then lithium iodide was added to dissolve, and a uniform lithium borohydride / lithium iodide mixed solution was formed by stirring at 25°C for 10 hours.

[0049] (2) Preparation of lithium borohydride-lithium iodide First, the lithium borohydride / lithium iodide mixed solution was transferred to a glass reaction tube with a valve, and the mixed solution was vacuum-desolventized by a vacuum device at 25°C. Secondly, the vacuum state was maintained, and after the solution was converted into a solid, the reaction tube was heated to 100°C at a rate of 3°C / min and heat-treated for 24 hours to obtain the product lithium borohydride-lithium iodide composite solid electrolyte material.

[0050] like Figure 1 As shown, X-ray powder diffraction (XRD) analysis shows that the obtained product is a lithium borohydride-lithium iodide complex without any other impurities. Figure 2 As shown, the scanning electron microscope (SEM) image shows that the lithium borohydride-lithium iodide complex is in the form of particles with a size between 3-5 μm.

[0051] Example 2 The difference from Example 1 is that lithium borohydride (3.08 g) and lithium iodide (9.5 g) are weighed at a molar ratio of 2:1. Specifically: A method for preparing a lithium borohydride-lithium iodide composite solid electrolyte material, the steps are as follows: (1) Preparation of lithium borohydride / lithium iodide solution Anhydrous tetrahydrofuran with a water content of 50 ppm was used as solvent, lithium borohydride and lithium iodide were used as raw materials, and lithium borohydride (3.08 g) and lithium iodide (9.5 g) were weighed at a molar ratio of 2:1. Lithium borohydride was first dissolved in 50 mL of tetrahydrofuran solution, and then lithium iodide was added to dissolve, and a uniform lithium borohydride / lithium iodide mixed solution was formed by stirring at 25°C for 10 hours.

[0052] (2) Preparation of lithium borohydride-lithium iodide First, the lithium borohydride / lithium iodide mixed solution was transferred to a glass reaction tube with a valve, and the mixed solution was vacuum-desolventized by a vacuum device at 25°C. Secondly, the vacuum state was maintained, and after the solution was converted into a solid, the reaction tube was heated to 100°C at a rate of 3°C / min and heat-treated for 24 hours to obtain the product lithium borohydride-lithium iodide composite solid electrolyte material.

[0053] Example 3 The difference from Example 1 is that the molar ratio of lithium borohydride (3.08 g) and lithium iodide (4.7 g) is 4:1. Specifically, a method for preparing a lithium borohydride-lithium iodide composite solid electrolyte material comprises the following steps: (1) Preparation of lithium borohydride / lithium iodide solution Anhydrous tetrahydrofuran with a water content of 50 ppm was used as solvent, lithium borohydride and lithium iodide were used as raw materials, and lithium borohydride (3.08 g) and lithium iodide (4.7 g) were weighed at a molar ratio of 2:1. Lithium borohydride was first dissolved in 50 mL of tetrahydrofuran solution, and then lithium iodide was added to dissolve, and a uniform lithium borohydride / lithium iodide mixed solution was formed by stirring at 25°C for 10 hours.

[0054] (2) Preparation of lithium borohydride-lithium iodide First, the lithium borohydride / lithium iodide mixed solution was transferred to a glass reaction tube with a valve, and the mixed solution was vacuum-desolventized by a vacuum device at 25°C. Secondly, the vacuum state was maintained, and after the solution was converted into a solid, the reaction tube was heated to 100°C at a rate of 3°C / min and heat-treated for 24 hours to obtain the product lithium borohydride-lithium iodide composite solid electrolyte material.

[0055] Example 4 A method for preparing a lithium borohydride-lithium iodide composite solid electrolyte material, comprising the following steps: (1) Preparation of lithium borohydride / lithium iodide solution Anhydrous tetrahydrofuran with a water content of 50 ppm was used as solvent, lithium borohydride and lithium iodide were used as raw materials, and lithium borohydride (3.08 g) and lithium iodide (6.3 g) were weighed at a molar ratio of 3:1. Lithium borohydride was first dissolved in 50 mL of tetrahydrofuran solution, and then lithium iodide was added to dissolve, and a uniform lithium borohydride / lithium iodide mixed solution was formed by stirring at a temperature of 10°C for 48 hours.

[0056] (2) Preparation of lithium borohydride-lithium iodide First, the lithium borohydride / lithium iodide mixed solution was transferred to a glass reaction tube with a valve, and the mixed solution was vacuum-desolventized by a vacuum device at 10°C. Secondly, the vacuum state was maintained, and after the solution was converted into a solid, the reaction tube was heated to 80°C at a rate of 2°C / min and heat-treated for 48 hours to obtain the product lithium borohydride-lithium iodide composite solid electrolyte material.

[0057] Example 5 A method for preparing a lithium borohydride-lithium iodide composite solid electrolyte material, comprising the following steps: (1) Preparation of lithium borohydride / lithium iodide solution Anhydrous tetrahydrofuran with a water content of 50 ppm was used as solvent, lithium borohydride and lithium iodide were used as raw materials, and lithium borohydride (3.08 g) and lithium iodide (6.3 g) were weighed at a molar ratio of 3:1. Lithium borohydride was first dissolved in 50 mL of tetrahydrofuran solution, and then lithium iodide was added to dissolve, and a uniform lithium borohydride / lithium iodide mixed solution was formed by stirring at 60°C for 3 hours.

[0058] (2) Preparation of lithium borohydride-lithium iodide First, the lithium borohydride / lithium iodide mixed solution was transferred to a glass reaction tube with a valve, and the mixed solution was vacuum-desolventized by a vacuum device at 60°C. Secondly, the vacuum state was maintained, and after the solution was converted into a solid, the reaction tube was heated to 150°C at a rate of 4°C / min and heat-treated for 6 hours to obtain the product lithium borohydride-lithium iodide composite solid electrolyte material.

[0059] Comparative Example Comparative Example 1 The difference from Example 1 is that in step (1), lithium borohydride and lithium iodide are added to the anhydrous tetrahydrofuran solution at the same time. The details are as follows: A method for preparing a lithium borohydride-lithium iodide composite solid electrolyte material, comprising the following steps: (1) Preparation of lithium borohydride / lithium iodide solution Anhydrous tetrahydrofuran with a water content of 50 ppm was used as solvent, lithium borohydride and lithium iodide were used as raw materials, and lithium borohydride (3.08 g) and lithium iodide (6.3 g) were weighed at a molar ratio of 3:1. Lithium borohydride and lithium iodide were added to 50 mL of tetrahydrofuran solution at the same time, and stirred for 10 hours at 25°C to form a uniform lithium borohydride / lithium iodide mixed solution.

[0060] (2) Preparation of lithium borohydride-lithium iodide First, the lithium borohydride / lithium iodide mixed solution was transferred to a glass reaction tube with a valve, and the mixed solution was vacuum-desolventized by a vacuum device at 25°C. Secondly, the vacuum state was maintained, and after the solution was converted into a solid, the reaction tube was heated to 100°C at a rate of 3°C / min and heat-treated for 24 hours to obtain the product lithium borohydride-lithium iodide composite solid electrolyte material.

[0061] The XRD pattern of the product lithium borohydride-lithium iodide composite solid electrolyte material is as follows Figure 5 As shown, a characteristic peak of lithium iodide-hydrate appears at the peak position of 20.6°, indicating that lithium iodide-hydrate is mixed in the product.

[0062] Comparative Example 2 The difference from Example 1 is that in step (1), lithium iodide is first added to the anhydrous tetrahydrofuran solution, and then lithium borohydride is added. The details are as follows: A method for preparing a lithium borohydride-lithium iodide composite solid electrolyte material, comprising the following steps: (1) Preparation of lithium borohydride / lithium iodide solution Anhydrous tetrahydrofuran with a water content of 50 ppm was used as solvent, lithium borohydride and lithium iodide were used as raw materials, and lithium borohydride (3.08 g) and lithium iodide (6.3 g) were weighed at a molar ratio of 3:1. Lithium iodide was first dissolved in 50 mL of tetrahydrofuran solution, and then lithium borohydride was added to dissolve. At a temperature of 25°C, a uniform lithium borohydride / lithium iodide mixed solution was formed by stirring for 10 hours.

[0063] (2) Preparation of lithium borohydride-lithium iodide First, the lithium borohydride / lithium iodide mixed solution was transferred to a glass reaction tube with a valve, and the mixed solution was vacuum-desolventized by a vacuum device at 25°C. Secondly, the vacuum state was maintained, and after the solution was converted into a solid, the reaction tube was heated to 100°C at a rate of 3°C / min and heat-treated for 24 hours to obtain the product lithium borohydride-lithium iodide composite solid electrolyte material.

[0064] The XRD pattern of the product lithium borohydride-lithium iodide composite solid electrolyte material is as follows Figure 6As shown, the characteristic peak of lithium iodide-hydrate also appears at the peak position of 20.6°, indicating that lithium iodide-hydrate is mixed in the product.

[0065] Comparative Example 3 The difference from Example 1 is that step (2) is directly heated to 100° C., and boiling occurs in the glass container, causing the mixed liquid to contaminate the pipeline system of the vacuum device.

[0066] Performance Testing The ionic conductivity of the lithium borohydride-lithium iodide composite electrolyte material of each embodiment and comparative example was measured and calculated by electrochemical impedance spectroscopy (EIS). The ionic conductivity measured at different temperatures using a stainless steel mold is shown in Table 1. In particular, the electrochemical impedance spectroscopy diagrams of Example 1 tested at 40°C and 120°C are shown in Table 1. Figure 3 and Figure 4 The electrochemical impedance diagrams of Example 2 tested at 40°C and 120°C are shown in Figure 7 and Figure 8 The electrochemical impedance diagrams of Example 3 tested at 40°C and 120°C are shown in Fig. 9 and Fig.10 middle.

[0067] Table 1. Ionic conductivity of lithium borohydride-lithium iodide composite electrolyte at different temperatures It can be seen from the above table that the lithium borohydride-lithium iodide composite electrolyte prepared in each embodiment of the present invention has excellent ionic conductivity.

[0068] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technician familiar with this profession can make some changes or modifications to equivalent embodiments of equivalent changes using the technical contents disclosed above without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent change and modification made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention still fall within the scope of the technical solution of the present invention.

Claims

1. A method for preparing a lithium borohydride-lithium iodide composite solid electrolyte material, characterized in that: The following steps are involved: A. Add lithium borohydride into anhydrous tetrahydrofuran solvent to dissolve it, and then add lithium iodide to form a uniform solution; B. Transfer the solution to a sealed container, remove the solvent in vacuum until the solution is converted into a solid; heat treatment is performed at a high temperature to obtain a composite solid electrolyte material.

2. The method for preparing the lithium borohydride-lithium iodide composite solid electrolyte material according to claim 1, characterized in that: The molar ratio of lithium borohydride to lithium iodide is 2-4:

1.

3. The method for preparing the lithium borohydride-lithium iodide composite solid electrolyte material according to claim 1, characterized in that: The volume of anhydrous tetrahydrofuran, the mass of lithium borohydride and lithium iodide and the ratio thereof are 2-8 mL:1 g.

4. The method for preparing the lithium borohydride-lithium iodide composite solid electrolyte material according to claim 1, 2 or 3, characterized in that: The dissolution temperature is 10-60 °C, and a uniform solution is formed by stirring for 3-48 h.

5. The method for preparing the lithium borohydride-lithium iodide composite solid electrolyte material according to claim 1, characterized in that: The sealed container is a glass reaction tube with a valve.

6. The method for preparing the lithium borohydride-lithium iodide composite solid electrolyte material according to claim 1, characterized in that: The temperature at which the solution is converted into the solid stage is 10-60 °C.

7. The method for preparing the lithium borohydride-lithium iodide composite solid electrolyte material according to claim 1, characterized in that: The heat treatment temperature is 80-150 ℃ and the time is 6-48 h.

8. The method for preparing the lithium borohydride-lithium iodide composite solid electrolyte material according to claim 1, 6 or 7, characterized in that: The heating rate is 2-4 °C / min.

9. Lithium borohydride-lithium iodide composite solid electrolyte material, prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the lithium borohydride-lithium iodide composite solid electrolyte material prepared by the preparation method according to any one of claims 1 to 8 in an all-solid-state battery.

Citation Information

Cited By

  • Solid electrolyte for lithium ion battery as well as preparation method and application of solid electrolyte

    CN122370485A

  • Solid-state electrolyte for lithium ion battery and preparation method and application thereof

    CN122370485B